Munc18-1 domain-1 controls vesicle docking and secretion by interacting with syntaxin-1 and chaperoning it to the plasma membrane - Han, Gayoung A. (The American Society for Cell Biology, 2011)
Munc18-1 plays pleiotropic roles in neurosecretion by acting as 1) a molecular chaperone of syntaxin-1, 2) a mediator of dense-core vesicle docking, and 3) a priming factor for soluble N-ethylmaleimide–sensitive factor attachment protein receptor–mediated membrane fusion. However, how these functions are executed and whether they are correlated remains unclear. Here we analyzed the role of the domain-1 cleft of Munc18-1 by measuring the abilities of various mutants (D34N, D34N/M38V, K46E, E59K, K46E/E59K, K63E, and E66A) to bind and chaperone syntaxin-1 and to restore the docking and secretion of dense-core vesicles in Munc18-1/-2 double-knockdown cells. We identified striking correlations between the abilities of these mutants to bind and chaperone syntaxin-1 with their ability to restore vesicle docking and secretion. These results suggest that the domain-1 cleft of Munc18-1 is essential for binding to syntaxin-1 and thereby critical for its chaperoning, docking, and secretory functions. Our results demonstrate that the effect of the alleged priming mutants (E59K, D34N/M38V) on exocytosis can largely be explained by their reduced syntaxin-1–chaperoning functions. Finally, our data suggest that the intracellular expression and distribution of syntaxin-1 determines the level of dense-core vesicle docking.